Summary : Office for Learning and Teaching Projects and Fellowships. - Office for Learning and Teaching (Office for Learning and Teaching, 2013)
This summary of projects and fellowships funded by the Office for Learning and Teaching was prepared for the National Learning Outcomes Standards Forum in Melbourne on 9 August 2013. The Forum sought to identify the core issues surrounding the implementation of national standards for learning outcomes and course design; explore the use of reference points for national learning outcomes standards; and recommend transparent, defensible and efficient mechanisms for demonstrating student achievement of learning outcomes.